The budget and appropriations committee report on the estimates of revenue and expenditure for financial year 2020/2021 - National Assembly (My University, 2020)
Mr Speaker, on behalf of the members of the budget and appropriations committee and as mandated by the article 221 of the constitution, section 39(2) of the PFM Act and standing orders 235(5), it is my pleasure to present to this house the committee's report on the estimates of revenue and expenditure for the financial year 2020/2021 and the medium term for the national government, parliament and the judiciary.
Keywords: estimates of revenue and expenditure; budget estimates